The Role of the Police in Investigating Alternative Evidence in Sexual Violence Cases Without Gynecological Visum Et Repertum in the Jurisdiction of Polda Metro Jaya - Dinanti Putri Dewa; Surya Nita; Zora Arfina (Transpublika Publisher, 2025)
The role of law enforcement in uncovering alternative evidence in sexual violence cases without gynecological visum et repertum is crucial to ensuring that cases can still be legally processed. By utilizing psychiatric visum, electronic evidence, forensic psychologist statements, and CCTV recordings, the police can build a strong case construction. Additionally, enhancing investigators' skills in trauma-informed interviewing and digital forensic investigation is essential for improving the effectiveness of investigations. However, law enforcement faces several challenges in collecting and utilizing non-physical evidence, including regulatory limitations, technical difficulties in digital forensics, socio-cultural factors that discourage victims from reporting, and a lack of interagency coordination. Therefore, strengthening investigator capacity, improving regulations, and fostering better collaboration with forensic psychologists and digital service providers are necessary to ensure non-physical evidence is widely accepted in the judicial system. To enhance the effectiveness of alternative evidence collection, the police must establish strong coordination with key stakeholders, such as the Witness and Victim Protection Agency (LPSK), forensic psychologists, the Integrated Service Center for Women and Children Empowerment (P2TP2A), and digital forensic institutions. Developing Standard Operating Procedures (SOPs), forming a Special Task Force for Sexual Violence Cases, and utilizing digital technology are key strategies for improving the accuracy and security of evidence. Moreover, public outreach is necessary to raise awareness of the importance of non-physical evidence in proving sexual violence cases. Through these strategies, law enforcement can ensure that cases are handled professionally, ultimately achieving justice for victims.